Effects of brief exposure to misinformation about e-cigarette harms on Twitter on knowledge and perceptions of e-cigarettes. (August 2022) - Liu, Jessica; Wright, Caroline; Elizarova, Olga; Dahne, Jennifer; Bian, Jiang; Williams, Philippa; Zulkiewicz, Brittany; Tan, Andy SL
Background: This study examined whether exposure to misinformation found on Twitter about e-cigarette harms leads to inaccurate knowledge and misperceptions of harms of e-cigarette use among cigarette smokers. Methods: We conducted an online randomized controlled experiment in November 2019 among an online sample of 2400 adult US and UK cigarette smokers who did not currently use e-cigarettes. Participants viewed four tweets in one of four conditions: 1) e-cigarettes are as or more harmful than smoking, 2) e-cigarettes are completely harmless, 3) e-cigarette harms are uncertain and 4) control (physical activity). Outcomes were knowledge about e-cigarettes and harm perceptions of e-cigarette use for five diseases. We conducted multiple logistic and linear regressions to analyze the effect of experimental conditions on outcomes, controlling for baseline knowledge and perceived harms. Findings: Participants in the 'as or more harmful' condition (vs. control group) had higher odds of accurate knowledge about e-cigarettes containing toxic chemicals ( p < 0.001), not containing only water vapor (p < 0.001) and containing formaldehyde ( p < 0.001). However, these participants had lower odds of accurate knowledge that e-cigarettes did not contain tar ( p < 0.001) and contained fewer toxins than cigarettes ( p < 0.001). Exposure to 'as or more harmful' tweets also increased harm perceptions for five diseases (all p < 0.001), with the greatest effect observed for lung cancer (β = 0.313, p < 0.001). This effect was greater among UK participants for all diseases. Interpretation: Brief exposure to misinformation on Twitter reduced accurate knowledge of the presence of tar and the level of toxins compared with smoking and increased harm perceptions of e-cigarette use.